2010
DOI: 10.1128/aac.01703-09
|View full text |Cite
|
Sign up to set email alerts
|

Telbivudine Exhibits No Inhibitory Activity against HIV-1 Clinical Isolates In Vitro

Abstract: Most approved drugs with activity against hepatitis B virus (HBV) have activity against human immunodeficiency virus type 1 (HIV-1), which precludes their use in patients who are coinfected with HBV and HIV-1 and who are not receiving antiretroviral therapy due to the risk of inducing resistance. The activity of telbivudine, a highly selective HBV inhibitor, against temporally and geographically distinct wild-type and multidrug-resistant HIV-1 clinical isolates was evaluated in vitro. No inhibition was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…It was clearly demonstrated that, in contrast to ETV, LdT does not exert an antiviral effect against wild-type as well as drug-resistant HIV strains. These virological data are in agreement with the data from Lin et al [10], who also reported no in vitro anti-HIV activity for LdT using the single-cycle PhenoSense™ assay (Monogram Biosciences, South San Francisco, CA, USA). Finally, we clearly demonstrate that, in contrast to ETV-MP, LdT-MP is not incorporated by wild-type HIV-1 RT.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It was clearly demonstrated that, in contrast to ETV, LdT does not exert an antiviral effect against wild-type as well as drug-resistant HIV strains. These virological data are in agreement with the data from Lin et al [10], who also reported no in vitro anti-HIV activity for LdT using the single-cycle PhenoSense™ assay (Monogram Biosciences, South San Francisco, CA, USA). Finally, we clearly demonstrate that, in contrast to ETV-MP, LdT-MP is not incorporated by wild-type HIV-1 RT.…”
Section: Discussionsupporting
confidence: 92%
“…Telbivudine (LdT), also known as l-thymidine, was approved for the treatment of chronic HBV infection in 2006. LdT in its 5′-TP form (LdT-TP) was shown previously to be a specific inhibitor of the HBV polymerase and did not demonstrate in vitro activity against HIV-1 [9][10][11]. This latter finding would make LdT a suitable candidate for the treatment of HIV-HBV-coinfected individuals without risking the…”
mentioning
confidence: 99%
“…Although a slight decrease in HIV-RNA was observed,68 no HIV mutation was found in vitro,69 suggesting that the supposed ‘anti-HIV activity of LdT’ might proceed from the consequence of HBV suppression and a direct immune modulating effect of LdT 70…”
Section: Hepatitis B: Remaining Challenges In Diagnosis Treatment Anmentioning
confidence: 99%
“…43 In vitro experiments, however, have not confirmed any anti-HIV activity for LdT. 44 On the other hand, LdT is a thymidine analogue and might share the same intracellular phosphorylation pathways with zidovudine (AZT) or stavudine (d4T). Thus, its use in combination must be avoided.…”
Section: Entecavir Adefovir and Telbiduvinementioning
confidence: 99%